2021
DOI: 10.1101/2021.05.19.21257433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

One year of SARS-CoV-2: Genomic characterization of COVID-19 outbreak in Qatar

Abstract: The state of Qatar has emerged as a major transit hub connecting all parts of the globe, making it as a hotspot for infectious disease introduction and providing an ideal setting to monitor the emergence and spread of variants. In this study, we report on 2634 SARS-CoV-2 whole-genome sequences from infected patients in Qatar between March-2020 and March-2021, representing 1.5% of all positive cases in this period. Despite the restrictions on international travel, the viruses sampled from the populace of Qatar … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Similar studies have been reported from a plethora of countries around the world including the UK, Ireland, Russia, India, Qatar etc. [26,[33][34][35][36]. These studies provide valuable information on the routes of importation of new strains and the emergence of critical mutations that change key parameters such as transmissibility or virulence, as was recently highlighted by the discovery of the B.1.617 variant and its B.1.617.2 sub-lineage in India [37], which led to a surge of SARS-CoV-2 infections in Delhi.…”
Section: Resultsmentioning
confidence: 98%
“…Similar studies have been reported from a plethora of countries around the world including the UK, Ireland, Russia, India, Qatar etc. [26,[33][34][35][36]. These studies provide valuable information on the routes of importation of new strains and the emergence of critical mutations that change key parameters such as transmissibility or virulence, as was recently highlighted by the discovery of the B.1.617 variant and its B.1.617.2 sub-lineage in India [37], which led to a surge of SARS-CoV-2 infections in Delhi.…”
Section: Resultsmentioning
confidence: 98%
“…Extended Data Figs. [1][2][3] show flowcharts depicting the selection of study populations to estimate effectiveness of BNT162b2 (Extended Data Fig. 1), mRNA-1273 vaccine (Extended Data Fig.…”
Section: Bnt162b2 and Mrna-1273 Covid-19 Vaccine Effectiveness Against The Sars-cov-2 Delta Variant In Qatarmentioning
confidence: 99%
“…In comparing estimates for Beta to those for Delta, it must be noted that the median PCR diagnosis date was 15 April 2021 for Beta cases, but was 2 August 2021 for Delta cases. Beta dominated transmission earlier in the study, whereas Delta dominated transmission later in the study [1][2][3][4][5] . From 1 August 2021 to 7 September 2021, 83.6% of the RT-qPCR-genotyped cases were Delta cases (Methods).…”
Section: Effectiveness Of Thementioning
confidence: 99%
See 2 more Smart Citations